A Comparative Study on the Microstructure Evaluation of Thixoforged A356 and A380 Aluminium Alloys - Guler, K. A.; Gecu, R.; Kisasoz, A.; Karaaslan, A. (CARL HANSER VERLAG, 2017)
Semi-solid processes of aluminium alloys have been a focus of interest for many years. Thixoforging is a kind of forging process which is carried out in the semi-solid region of the alloy. Ingots used in thixoforging process cannot be produced by conventional ways; they must be prepared with different processing routes. In this study, low superheat casting (LSC) technique was used for ingot fabrication in thixoforging process. LSC can be summarized as the pouring of molten metal at a temperature very close to liquidus followed by rapid solidification. Low heat input combined with sudden cooling suppresses dendritic growth and the conventional casting structure converts into a more spherical structure. A356 and A380 are well-known casting aluminium alloys which are commonly used in sand and die casting processes. These alloys are appropriate for semi-solid process and there are many applications that researches have been carried out in time. In view of that, A356 and A380 alloys were selected as subject of this comparative study and final structures were evaluated together. A LSC combined thixoforging process was successfully applied to both alloys and a spherical microstructure was obtained. High sphericity with a simple microstructure is the characteristic of the A356 alloy. A380 shows relatively lower sphericity with more complex microstructure which has numerous different intermetallic compounds.
Keywords: EVOLUTION; Metallurgy & Metallurgical Engineering